Addis Dialogue: Featuring ILRI Director-General - Djikeng, Appolinaire (EBC ENGLISH, 2025)
Director-General of the International Livestock Research Institute (ILRI) and Senior Director for the Livestock-based systems of the CGIAR, Professor Appolinaire Djikeng has spent some time with Addis Dialogue on EBC WORLD. He says Ethiopia has the potential to feed the entire Africa and beyond. He also says a very strong leadership is being witnessed recognizing the fact that the livestock sector is a key contributor for GDP in the Horn.